Information content and informativeness of analysts’ report: evidence from Malaysia - Mohd Thas Thaker, Hassanudin; Mohamad, Azhar; Mustaffa Kamil, Nazrol Kamil; Duasa, Jarita (Emerald, 2019)
Purpose This study aims to document the influence of information content and the informativeness of analyst reports towards cumulative abnormal return (CAR) in the Malaysian market.